PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PUBLIK PADA KANTOR KECAMATAN MENGGALA KABUPATEN TULANG BAWANG - Asmaria Asmaria; M Fikri Akbar; Mey Ningsih Marbun (e-JKPP, 2021)
The essence of local government in an area is to provide services to the community both in terms of quality and quantity, which means that the government as a public servant is required to "perform" well so that it has an impact on increasing community satisfaction. The purpose of this study was to analyze the effect of tangibles, reliability, responsiveness, assurance and empathy on public satisfaction at the Menggala District Office, Tulang Bawang Regency, either partially or simultaneously . The data collection techniques in this study were observation, questionnaires and documentation. The population in this study amounted to 58 people. The research method uses associative descriptive method. In this study the authors used qualitative and quantitative data analysis.In general, the results of this research are as follows: 1) Tangibles have a positive effect on public satisfaction at the Menggala District Office, Tulang Bawang Regency, 2) Reliability has a positive effect on public satisfaction at the Menggala District Office, Tulang Bawang Regency, 3) Responsiveness has a positive effect on public satisfaction at the Menggala District Office, Tulang Bawang Regency, 4) Assurance has a positive effect on public satisfaction at the Menggala District Office, Tulang Bawang Regency, 5) Empathy has a positive effect on public satisfaction at the Office Menggala District, Tulang Bawang Regency and 6) Tangibles, reliability, responsiveness, assurance and empathy together have a positive effect on public satisfaction at the Menggala District Office, Tulang Bawang Regency.